Analgesic and anti-diarrhoeal activities of Lagerstroemia speciosa roots in experimental animal model (Dhaka University Journal of Pharmaceutical Sciences, 2015)
The methanolic crude extract of Lagerstroemia speciosa roots was investigated for its possible analgesic and anti-diarrhoeal activities in experimental animal model. Phytochemical screening of the methanolic extract of L. speciosa roots showed the presence of alkaloids, flavonoids, saponins, tannins and reducing sugar. In acute toxicity study, no mortality or toxic reaction was recorded in animal model after administration of the L. speciosa roots extract. Analgesic activity was evaluated by using acetic acid induced writhing inhibition method in Swiss albino mice. In peripheral method of anti-nociception, the methanolic crude extract of L. speciosa roots showed significant analgesic activity. At the dose of 200 and 400 mg/kg body weight, the extract produced 35.38% and 53.85% (P